Evidence that DNA polymerase δ contributes to initiating leading strand DNA replication in Saccharomyces cerevisiae - Marta A. Garbacz (Nature Portfolio, 2018)
DNA polymerases δ and ε (Pols δ and ε) are thought to be responsible for lagging and leading strand synthesis, respectively. Here the authors present evidence that Pol δ contributes to the initiation of leading strand replication in budding yeast by synthesizing DNA of both strands at replication origins.